Pemanfaatan Fungsi Taman Suropati Menteng sebagai Taman Kota - Suesilowati; Priyoto; Muhammad Zaki Afandi (Bulletin of Community Engagement, 2024)
This article Utilize the Function of Suropati Menteng Park as a City Parkhe. The samples used were the manager of Suropati Menteng Park and visitors to Suropati Menteng Park. The purpose of this study is to find out the functioning of Suropati Menteng park in the functioning of social functions and to find out the functioning of aesthetic functions in Suropati Menteng park. This type of research is field research which means observing directly the object being researched with the aim of obtaining relevant data. This research is a type of descriptive quantitative research where researchers can obtain data collected in the form of processed numbers. The results of the research that has been carried out by taking 60 respondents by including respondent data. This research includes age, gender, and domicile. The results of this study show that the functioning of Suropati Park on social and aesthetic functions is quite good, because of the 60 respondents the results of the questionnaire that were distributed showed agreement with the statement that had been made by the author. The average value of the perception given by visitors to this aspect is 3.1 which means agree. This score can be said to be in the high category. This condition indicates that Suropati Park is quite good in carrying out social functions. Assessment points in this aspect include an assessment of the cleanliness of the garden environment and beauty. The average score for this aspect is 3.1 which means agree.